Latin America and the Caribbean Meet the Post-Soviet World: Can Pro Forma Diplomacy Evolve? - W. A. Sanchez (Международная аналитика, 2021)
The 33 countries that constitute Latin America and the Caribbean and the 11 countries of the former Soviet Union (not counting the Russian Federation and the three Baltic nations) conform 44 states which are, with a few exceptions, on the periphery of global geopolitical aff airs, with limited international infl uence or at the mercy of confl icts that have disrupted their internal balance and international image in the past decade. While the topic of how peripheral nations and regions interact with each other has been analyzed in academia, in-depth studies about relations between these specifi c regions are very limited and scarce. This paper seeks to fi ll in that gap by providing recent examples on issues like trade and high-profi le diplomatic visits between Latin American and Caribbean governments with their post-Soviet counterparts. Moreover, I will discuss the issue of the location (or lack thereof) of embassies, a topic not discussed in the consulted literature, as an example of how governments from peripheral states and limited budgets decide where to open an embassy. It is proposed here that the 44 states that make up Latin America, the Caribbean, and the post-Soviet world will remain cordial and friendly strangers for the foreseeable future. A lack of grand-strategy vision, with a few exceptions, is a major hindrance to stronger relations between these states. The most plausible scenario is bloc-to-bloc trade agreements; however, the COVID-19 pandemic and more pressing issues that these countries face mean that treaties with geographically distant states that are not trading partners or potential sources of fi nancial aid are not regarded as priorities.